Developing Solutions and Informing Irish Policymakers across the Pillars of Climate, Water, and Sustainability - Stewart, Dorothy (Statistical and Social Inquiry Society of Ireland, 2020)
This paper provides a brief overview of the Environmental Protection Agency (EPA) Research programme within the context of the science policy interface. The paper asserts that robust evidence is necessary to inform the development and implementation of policy in a meaningful and impactful way. The paper focuses on tools developed to improve the science policy interface by providing opportunities where EPA funded research can ‘Bridge the Gap’ between science and policy. Examples are presented under the three pillars of Climate, Water and Sustainability, to demonstrate how EPA funded research project outputs have informed policy. It is acknowledged from the outset that several factors influence the science policy interface and this short paper proposes some solutions to inform this broad and arena.
Edited transcript of presentation before the Society, 23rd April 2020 - Symposium: Science-Policy Interfaces and the Environment
Keywords: Science policy interface; evidence; collaboration; knowledge transfer; 314.15